Analisis Kinerja Kompressor Screw Oil Injected Sullair Ls20-150h untuk Ash Handling (Study Kasus PLTU Teluk Sirih) - Abdillah, Muhammad; Mukhnizar, Mukhnizar; Abu , Risal; Afdal , Afdal; Zulkarnain, Zulkarnain (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PLTU Teluk Sirih is a coal-fired steam power plant as an energy source that produces ash with a capacity of 2 . The compressor is a medium for transferring ash by using compressed air. The compressor used is a SCREEW OIL INJECTED SULLAIR LS20-150H compressor. Currently there is a decrease in performance on the compressor, which initially had a compression ratio of 1,600 Psia, polytropic head 14,500,599, capacity 10,938,438, flow rate 11,379,622 lb/s, efficiency 98.5%. After analyzing this compressor, the data obtained was a compression ratio of 1,540 Psia, polytropic head 13,805,166, capacity 10,950,733, flow rate 11,392,412, and efficiency of 95.3%. The reason is because the compressor room area does not have an active blower so that dirt/ash stuck to the radiator fins causes heat transfer to be hampered and this greatly affects the performance of the compressor parts to work optimally